2009
DOI: 10.1177/1078390309343713
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Differential Item Functioning of the CES-D Scale According to Caregiver Status and Cultural Context in Korean Women

Abstract: BACKGROUND Proper evaluation of the generalizability of an instrument is critical for its use across different social contexts such as caregiver status. OBJECTIVE To examine the differential item functioning of the Center for Epidemiologic Studies Depression (CES-D) Scale, patterns of response to each item of the CES-D Scale attributable to caregiver status was assessed. STUDY DESIGN Using a cross-study comparison method, a sample of 58 matched pairs of Korean American caregivers and noncaregivers was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Conditional on positive affect, non-Hispanic Black as contrasted with non-Hispanic White respondents evidenced a lower probability of endorsing the item, “lonely”. DIF has been observed for items related to loneliness in other studies, specifically with respect to age (Choi et al 2009; Estabrook et al 2015). …”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Conditional on positive affect, non-Hispanic Black as contrasted with non-Hispanic White respondents evidenced a lower probability of endorsing the item, “lonely”. DIF has been observed for items related to loneliness in other studies, specifically with respect to age (Choi et al 2009; Estabrook et al 2015). …”
Section: Discussionsupporting
confidence: 60%
“…Differential item functioning has been observed for happiness items with respect to age (Choi et al 2009; Estabrook et al 2015); education in the direction of lower education associated with higher happiness, conditional on depression (Perkins et al 2006); and gender (Yin et al 2015). In the latter study, conditional on the depression trait, men were less likely to endorse being happy.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies that have reported reliability coefficients for negative affect items and positive affect items separately, the reliability of items were inconsistently different between Blacks and Whites ( 11 , 36 , 37 ). Considering that depressive symptoms are subject to variations under different psychosocial and clinical situations, both of which are different in Blacks and Whites ( 26 32 ), reliability analyses of CES-D scale may have an implication that depressive symptoms are represented differently in Blacks and Whites ( 33 , 34 ), whether due to the differences in their living conditions or item-specific differences in the responses given by each ethnic group ( 35 ). In the later case, it seems that the endorsement rate of certain CES-D items can be different between Whites and Blacks, for example, Whites, especially White women, less likely respond positively to the item “people are unfriendly” ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, the reliability of measures of depressive symptoms may be influenced by psychosocial factors as well as clinical conditions ( 26 , 27 ), both factors are differently distributed in Blacks and Whites ( 28 32 ). Some studies imply that CES-D score may differently represent true depression in Whites and Blacks ( 33 , 34 ). In addition, there have been inconsistent results comparing the reliability of CES-D scale across ethnic groups ( 11 , 13 , 35 – 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we selected only Korean American women for this study because of their accessibility and willingness to share their thoughts and experiences concerning health issues. In addition, as in all other ethnic groups (U.S. Department of Health and Human Services, 2005), women are typically the primary family caregivers in the Korean community (Choi, Fogg, Lee, & Wu, 2009).…”
Section: Setting and Participantsmentioning
confidence: 99%